An Evaluation of a Syndromic Molecular Panel in Optimising the Microbiological Diagnosis and Antimicrobial Therapy of Suspected Osteoarticular Infections in Paediatric Patients - Marilena Agosta; Venere Cortazzo; Manuela Onori; Barbara Lucignano; Gianluca Vrenna; Martina Rossitto; Maria del Carmen Pereyra Boza; Valeria Fox; Marco Roversi; Antonio Musolino; Andrzej Krzysztofiak; Laura Lancella; et al. (Diagnostics)
Background/Objectives: Paediatric osteoarticular infections (POAIs) present unique diagnostic and therapeutic challenges. Microbiological culture (MC) is typically time-consuming and lacks sensitivity, especially when patients have received antibiotics. The BIOFIRE® Joint Infection Panel (BJIP) is a syndromic molecular assay for the direct identification of most pathogens causing POAIs. Methods: We evaluated BJIP in 17 synovial fluids, and then, we retrospectively assessed its utility in 93 off-label specimens (i.e., 25 purulent fluids/biopsies and 68 whole blood samples). All specimens were collected from October 2022 to March 2024 from paediatric patients admitted at the Bambino Gesù Children’s Hospital in Rome. Results: A bacterial pathogen was isolated in only one of 17 synovial fluid cultures, while BJIP identified eight additional microorganisms in MC-negative cases. The most frequently detected pathogen was S. aureus (44.5%, 4/9). BJIP performance in synovial fluids showed an overall positive percentage agreement (PPA) and negative percentage agreement (NPA) of 100% and 88.1%, respectively, compared to MC. All positive results (n/N = 9/17) were considered medically significant, with an increase in NPA to 100%. In purulent fluids/biopsies, BJIP and MC were concordant in 72% of cases (n/N = 18/25), with a per-sample PPA and NPA of 90% and 60%, respectively. For whole blood samples, almost all samples were negative by both methods (i.e., reference blood culture and BJIP), and the molecular test did not enable any further microbiological diagnosis. Conclusions: The BIOFIRE® Joint Infection Panel rapidly and accurately enabled or excluded a diagnosis of a POAI (~1 vs. 24–96 h for MC), optimising antimicrobial therapy.